Tetrandrine reduces oxidative stress, apoptosis, and extracellular matrix degradation and improves intervertebral disc degeneration by inducing autophagy. Issue 2 (1st February 2022) - Liu, Jintao; Yu, Pengfei; Dai, Feng; Jiang, Hong; Ma, Zhijia
ABSTRACT: Tetrandrine (TET) was reported to be an autophagy agonist, and the activating autophagy could delay intervertebral disc degeneration (IDD). Our study focused on exploring whether TET attenuated tert butyl hydrogen peroxide (TBHP)-induced nucleus pulposus (NP) cell injury and delayed rat IDD by inducing autophagy. In vitro, cytotoxicity was detected by MTT assay, ROS was measured with DCFH-DA probe, MDA, and SOD content was evaluated through ELISA, NP cell apoptosis was tested by flow cytometry, protein expression was detected by Western blot, in particular, LC3 expression was assessed by immunofluorescence. In vivo, pathological changes were estimated by HE and safranin-O staining, related protein expression was measured by immunohistochemistry, and the apoptosis was detected by TUNEL. Compared with the control group, oxidative stress, apoptosis, and extracellular matrix (ECM) degradation were increased, the expression of cleaved caspase-3, 9, aggrecan and collagen II were reduced, and the expression of MMP13 and ADAMTS5 were up-regulated in TBHP-treated NP cells. Moreover, TET could reverse the effect of TBHP on NP cells. Further, TET enhanced autophagy in NP cells by amplifying the LC3 II/LC3 I/ratio and reducing p62 expression, which attenuated oxidative stress, apoptosis, and ECM degradation in TBHP-treated NP cells. In addition, in vivo, TET delayed rat IDD, increased the expression of LC3 and collagen II, and weakened apoptosis. TET inhibited oxidative stress, apoptosis, and ECM degradation in TBHP-treated NP cells by inducing autophagy, and alleviated IDD. These indicated that TET might be a potential candidate drug for the treatment of IDD. Graphical abstracts: uf0001